Strengthening Mahārah al-Qirā’ah through the Sorogan Strategy: A Study of Kitab Turāts Learning at Pondok Pesantren Al-Khoirot Malang - Muhlis, Nur Khozim; Imawan, Yuli; Afifi, A. Nawawi Alfan; Fahrudin, Fahrudin; Zaironi, Muhammad (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study investigates the implementation of the sorogan strategy in mahārah al-qirā’ah (reading skills) instruction at Pondok Pesantren Al-Khoirot, Malang. The sorogan method fosters a rigorous learning environment where students demonstrate their reading proficiency directly before the Kiai. This research aims to describe the planning and execution of mahārah al-qirā’ah instruction through the sorogan strategy in the context of reading Turats (classical) books. Employing a descriptive qualitative approach, data were gathered from teachers and students through observations and interviews. The analysis followed a systematic process of data collection, processing, presentation, and conclusion drawing. The findings demonstrate that this strategy significantly enhances students' in-depth comprehension and ability to read Turats books, particularly in grammatical analysis (Qawaid) and textual interpretation. This success is attributed to the dual support system: students' intensive preparation via the muthola’ah (independent study) system in peer groups and direct pedagogical guidance from the Kiai during the session. While previous research has evaluated the sorogan method using the CIPP model in different settings, this study emphasizes the procedural integration of independent and guided learning. These findings offer theoretical and practical implications for designing effective mahārah al-qirā’ah instruction within traditional Islamic educational frameworks.